Retinoic Acid Mediated Clearance of Citrobacter rodentium in Vitamin A Deficient Mice Requires CD11b+ and T Cells - Snyder, Lindsay M.; McDaniel, Kaitlin L.; Tian, Yuan; Wei, Cheng-Hsin; Kennett, Mary J.; Patterson, Andrew D.; Ross, A. Catharine; Cantorna, Margherita T. (Frontiers in Immunology, 2019)
Vitamin A deficiency affects over 250 million preschool-age children worldwide and is associated with increased childhood mortality and risk of developing enteric infections. Vitamin A deficient (A-) mice developed chronic Citrobacter rodentium infection. A single oral dose of retinoic acid (RA) at d7 post-infection was sufficient to induce clearance of the pathogen in A- mice. RA treatment of A- mice induced il17a expression in the colon. In A- mice, colonic IL-17 was primarily produced by CD11b+ cells; however, in A+ mice, the major source of colonic IL-17 was CD4+ T cells. To determine the cellular targets of vitamin A required for host resistance to C. rodentium, mice that express a dominant negative (dn) retinoic acid receptor (RAR) in T cells (T-dnRAR) or macrophage/neutrophils (LysM-dnRAR) were used. T-dnRAR mice had T cells that produced a robust intestinal IL-17 response and for 40% of the mice was enough to clear the infection. The remainder of the T-dnRAR mice developed a chronic infection. A- LysM-dnRAR mice developed early lethal infections with surviving mice becoming chronically infected. RA treatment of A- LysM-dnRAR mice was ineffective for inducing colonic IL-17 or clearing C. rodentium. Retinoid signaling is required in T cells and CD11b+ cells for complete elimination of enteric pathogens.